'Out of the loop': early childhood educators gaining confidence with unfamiliar policy discourse. Issue 4 (2nd October 2017) - Kilderry, Anna; Nolan, Andrea; Scott, Caroline
Abstract: It has been seven years since the Early Years Learning Framework (EYLF) was introduced in Australia and four years since the National Quality Standard (NQS) was implemented. To gain insight into how educators are understanding practice in the Australian early childhood and care context, the study draws on a praxeological frame where educators have the opportunity to inquire and critically reflect on practice in a supported research environment. Data were analysed using critical discourse analysis, enabling a close examination of participant reflections and understandings about practice. Findings reveal that educators are confident when describing their teaching using familiar educational discourse, whereas educators were apprehensive when confronted with new and unfamiliar concepts. The third finding illustrates the ways educators gain confidence with unfamiliar policy discourse. The study's findings add to limited empirical evidence about how early childhood educators understand key concepts introduced by the EYLF and NQS.